Identification of a Conserved Prophenoloxidase Activation Pathway in Cotton Bollworm Helicoverpa armigera - Wang, Qianran; Yin, Mengyi; Yuan, Chuanfei; Liu, Xijia; Hu, Zhihong; Zou, Zhen; Wang, Manli (Frontiers in Immunology, 2020)
Melanization is a prominent insect humoral response for encapsulation of and killing invading pathogens. It is mediated by a protease cascade composed of a modular serine protease (SP), and clip domain SPs (cSPs), which converts prophenoloxidase (PPO) into active phenoloxidase (PO). To date, melanization pathway in cotton bollworm Helicoverpa armigera, an important agricultural pest, remains largely unclear. To biochemically reconstitute the pathway in vitro, the putative proteases along with modified proteases containing the factor Xa cleavage site were expressed by Drosophila S2 cell expression system. Purified recombinant proteins were used to examine their role in activating PPO. It is revealed that cascade is initiated by a modular SP-SP41, followed by cSP1 and cSP6. The three-step SP41/cSP1/cSP6 cascade could further activate PPO, and the PO activity was significantly enhanced in the presence of two cSP homologs (cSPHs), cSPH11 and cSPH50, suggesting the latter are cofactors for PPO activation. Moreover, baculovirus infection was efficiently blocked by the reconstituted PPO activation cascade, and the effect was boosted by cSPH11 and cSPH50. Taken together, we unraveled a conserved PPO activation cascade in H. armigera, which is similar to that exists in lepidopteran biochemical model Manduca Sexta and highlighted its role in antagonizing viral infection.